2019
DOI: 10.4244/eij-d-19-00247
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic valve endocarditis after transcatheter or surgical aortic valve replacement with a bioprosthesis: results from the FinnValve Registry

Abstract: Aims:The aim of this study was to compare the risk of prosthetic valve endocarditis (PVE) in patients with transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR). Methods and results:The FinnValve registry included data from 6,463 consecutive patients who underwent TAVR (n=2,130) or SAVR (n=4,333) with a bioprosthesis from 2008 to 2017. PVE was defined according to the modified Duke criteria. In this study, the incidence of PVE was 3.4/1,000 person-years after TAVR, and 2.9/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
4
40
0
Order By: Relevance
“…Both staphylococci and streptococci were isolated in about 30% of cases and Enterococcus was found in one-fourth of the patients. These results fully align with previous findings in patients with TAVI infective endocarditis [11,16,58,59].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both staphylococci and streptococci were isolated in about 30% of cases and Enterococcus was found in one-fourth of the patients. These results fully align with previous findings in patients with TAVI infective endocarditis [11,16,58,59].…”
Section: Discussionsupporting
confidence: 92%
“…Infection of TAVI prostheses is not uncommon, with a reported incidence of 0.5-1.6% per year in populations followed up to 5 years; the concomitant survival rate is 40-50% [12,[54][55][56]. Review papers [18,57,58] and analyses of national and international registries [11][12][13][14]16] have started delineating the common features of TAVI prosthesis infection and have ultimately highlighted two important findings: patients with TAVI endocarditis suffer a dismal early outcome with a mortality of 40-70% at 1 year after the diagnosis, and surgical explantation of the infected prosthesis was performed in only 2-14% of cases despite clear indications for surgical intervention in more than 80% of patients [11,13,14,16,41,59]. Reasons for not operating include a remarkably high clinical or surgical risk, need for additional procedures, advanced age of the patient and limited life expectancy, multiorgan failure, septicaemia and dismal long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A temporary pacing lead may also be an entry point for bacteria into the bloodstream. Staphylococcus aureus was the cause of PVE in 25% of the patients, which was comparable with the findings of other studies [17,23].…”
Section: Discussionsupporting
confidence: 91%
“…Mortality in IE is one of the highest among heart-related diseases; it can reach up to 24% for native valve IE (Cresti et al, 2017) and surpass 46% for PVE (Akowuah et al, 2003). Moriyama et al (2019) reported 30-days and one-year mortality in TAVI-IE of 37.7% and 52.5%. In the pooled series, it was 38.3% for overall reported follow up.…”
Section: Discussionmentioning
confidence: 99%